Análisis del plan de mantenimiento de los equipos informáticos de la Unidad Educativa Emigdio Esparza Moreno. - Campos Muñoz, Adonis Gerardo (2022)
The recent case study project contains a plan for the maintenance of the Software based on remote access implemented in the Emigdio Esparza Moreno educational unit where for several years the machines of the establishments have already been totally abandoned due to the pandemic in In 2019, these computers are presumed to be used in this new school year 2022, which will have modern applications by technology that has advanced by leaps and bounds even more in this period of pandemic where it has been used in most of the jobs and even at home all kinds of technological tools. In the first part, it describes the problem about computers, which were on hiatus for several years, it is intended to revive the equipment through technology and the operators are trained people with the necessary knowledge to use this tool and work long distance. So as not to have direct contact with these people who are outside the curriculum required by the educational unit. The Emigdio Esparza Moreno Educational Unit not only requires this technological tool for the implementation of maintenance on the computers, but also so that teachers can control their students at the time they teach their class, this tool has multiple advantages which the educational unit intends to make the most of them. The Emigdio Esparza Moreno Educational Unit not only requires this technological tool for the implementation of maintenance on the computers, but also so that teachers can control their students at the time they teach their class, this tool has multiple advantages which the educational unit intends to make the most of them.